Tasawwuf and western interests perspective of history and politics - Ladjal, Tarek; Bensaid, Benaouda; Roslan, M. Noor (Center for Study of Religion and Religious Tolerance, 2012)

(untitled)
This relationship between Sufism and politics presents itself at the heart of an emerging Western interest in Sufi political development. Western institutions have identified Tasawwuf as viable option for shaping all forms of cooperation and understanding with the Muslim world. Such a choice however, stems from factual realities shown in the practice of some Sufi schools and historical developments. This inquiry seeks to explore the historical context of Sufism in relation to political engagement while elucidating its course of interaction as a demonstration of its very values and ideals. This paper also examines some of the similarities and differences between the attitudes of classical and contemporary Sufi practices vis-à-vis political life, and evaluates the evidences of both the current approaches to and interpretation of the position of Sufism in today’s world. This research demonstrates the partial interpretation that favors a particular trend pertaining to Sufism and politics, and suggests that the defiant and politically active interpretation of Tasawwuf is by large the dominant and historically consistent current in Sufi thought and practice.